The Use of Rubric: an Opportunity to Promote Thinking and Learning - Herawati, Agnes (Bina Nusantara University, 2011)
Article discusses the ways in which students perceive and use rubrics to support learning in the classroom. To further examine the impact of rubrics on students learning, this study conducted how rubrics gave impact on students learning, as well as whether using rubrics influenced the thinking ability of the students. In this study, 34 undergraduate students were provided rubrics for each of the two writing assignments assigned during the semester. At the end of the second assignment, students were asked about the use of rubrics as well as the relationship between rubric and performance. The students said that using rubrics helped them focus their efforts, produce work on higher quality and get better marks